2014
DOI: 10.1063/1.4874803
|View full text |Cite
|
Sign up to set email alerts
|

Fast generation of domain walls with defined chirality in nanowires

Abstract: Currentinduced coupled domain wall motions in a twonanowire system Appl. Phys. Lett. 99, 152501 (2011) The effect of geometrical confinement and chirality on domain wall pinning behavior in planar nanowires J. Appl. Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The circuit model not only provides a useful picture for understanding the magneto-transport properties, but also serves as a guiding principle for designing artificial spin-ices as reconfigurable magneto-resistive devices. One of the novel features of artificial spin ice is the potential to manipulate these emergent magnetic charge degrees of freedom, for example, through local injection of domain walls into the nanowires [35][36][37]. We expect our method provide a useful tool to further understand the intriguing interplay of magnetic charges and magnetotransport in artificial spin ice.…”
Section: Discussion and Outlookmentioning
confidence: 95%
“…The circuit model not only provides a useful picture for understanding the magneto-transport properties, but also serves as a guiding principle for designing artificial spin-ices as reconfigurable magneto-resistive devices. One of the novel features of artificial spin ice is the potential to manipulate these emergent magnetic charge degrees of freedom, for example, through local injection of domain walls into the nanowires [35][36][37]. We expect our method provide a useful tool to further understand the intriguing interplay of magnetic charges and magnetotransport in artificial spin ice.…”
Section: Discussion and Outlookmentioning
confidence: 95%
“…The possibility to generate DWs with defined chirality was found recently through MTXM studies by creating vortex DWs in permalloy nanowires through nanosecond long current pulses with varying polarity and adjusting the alignment between the stripline and the nanowire [200].…”
Section: B Magnetic Dwsmentioning
confidence: 99%
“…How to manipulate the chirality and polarity of vortex walls moving on magnetic stripes is a challenging issue, mainly because of the difficulty in obtaining good-to-noise ratio with single object measurements and not in arrays, as it has been done in most of the work reported so far. Some recent papers have reported experimental [10][11][12][13][14][15], and simulation [16] data about the dynamics of domain walls in Permalloy (Py) nanowires with notches, walls driven by magnetic field and/or spin polarized current. These authors have demonstrated that notches with different geometries (squares or triangular) provide different potential barriers to the domain walls, which in turn can be transversal or vortex walls [17,18].…”
Section: Introductionmentioning
confidence: 99%